Modeling ordered choices a primer - Greene, William H. 1951-; Hensher, David A. 1947-. (Cambridge Cambridge University Press, 2010)
A synthesis of developments in ordered choice modeling over the past fifty years.
Introduction : random utility and ordered choice models -- Modeling binary choices -- A model for ordered choices -- Antecedents and contemporary counterparts -- Estimation, inference and analysis using the ordered choice model -- Specification issues and generalized models -- Accommodating individual heterogeneity -- Parameter variation and a generalized model -- Ordered choice modeling with panel and time series data -- Bivariate and multivariate ordered choice models -- Two-part and sample selection models -- Semiparametric and nonparametric estimators and analyses.
Acquired through Health Policy Development Program (HPDP) research grant.
Keywords: Order statistics; Goodness-of-fit tests